2015
DOI: 10.1371/journal.pone.0133047
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cryptosporidium Species in Fish from Lake Geneva (Lac Léman) in France

Abstract: Cryptosporidium, a protozoan parasite that can cause severe diarrhea in a wide range of vertebrates including humans, is increasingly recognized as a parasite of a diverse range of wildlife species. However, little data are available regarding the identification of Cryptosporidium species and genotypes in wild aquatic environments, and more particularly in edible freshwater fish. To evaluate the prevalence of Cryptosporidiumspp. in fish from Lake Geneva (Lac Léman) in France, 41 entire fish and 100 fillets (cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 28 publications
(46 reference statements)
6
46
0
1
Order By: Relevance
“…Previous studies have also reported large variation in prevalences ranging from 0.8 to 100% (Sitjà-Bobadilla et al, 2005;Murphy et al, 2009;Reid et al, 2010;Zanguee et al, 2010;Morine et al, 2012;Koinari et al, 2013;Certad et al, 2015;Ryan et al, 2015). In the present study, the majority of fish screened were ornamental fish, for which the prevalence was 7.0% (38/545).…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Previous studies have also reported large variation in prevalences ranging from 0.8 to 100% (Sitjà-Bobadilla et al, 2005;Murphy et al, 2009;Reid et al, 2010;Zanguee et al, 2010;Morine et al, 2012;Koinari et al, 2013;Certad et al, 2015;Ryan et al, 2015). In the present study, the majority of fish screened were ornamental fish, for which the prevalence was 7.0% (38/545).…”
Section: Discussionsupporting
confidence: 48%
“…In that study, the prevalence of C. parvum was 86.7% (13/15), the prevalence of C. molnari was 6.7% (1/15) and 6.7% (1/15) were mixed C. parvum and C. molnari infections (Certad et al, 2015). C. molnari was identified in the stomach, while developmental stages of C. parvum were found in the stomach and intestine indicating that C. parvum is infecting fish, rather than being passively, carried which has important public health implications.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Of these, only C. parvum , C. hominis and C. scrofarum are of public health interest. Cryptosporidium scrofarum was identified in a whiting (Reid et al., 2010); C. parvum was found in School whiting, Nile tilapias, a Silver barb, Arctic char and European whitefish and C. hominis was reported in Mackerel scad (Reid et al., 2010, Gibson-Kueh et al., 2011, Koinari et al., 2013, Certad et al, 2015). In one of the most recent studies, C. parvum was identified in freshwater fish from Lake Geneva (Lac Léman) by both histology and molecular analysis (Certad et al., 2015).…”
Section: Wildlife Associated Outbreaks and Water Contaminationmentioning
confidence: 99%